Compulsive "grazing" and addictive tendencies towards food. (26th September 2018) - Bonder, Revi; Davis, Caroline; Kuk, Jennifer L.; Loxton, Natalie J.
Abstract: Evidence suggests that palatable foods can promote an addictive process akin to drugs of abuse. To date, research in the field of food addiction has focused largely on binge eating as a symptom of this condition. The present study investigated relationships between food addiction and other patterns of overeating, such as compulsive grazing—a behaviour with high relevance to bariatric surgery outcomes. Adults between the ages of 20 and 50 years ( n = 232) were recruited for the study. Participants completed questionnaires to assess various eating behaviours and related personality measures. Regression analysis employed the Yale Food Addiction Scale (YFAS) as the dependent variable. Results indicated that addictive personality traits, reward‐driven eating, and compulsive grazing each contributed unique variance to the YFAS symptom score. These findings provide novel insight into the association between a grazing pattern of overeating and food addiction, and emphasize that similar to traditional addiction disorders such as alcoholism, binge consumption is not the only pattern of compulsive intake.